Self-assessment in musculoskeletal pathology x-rays - Sakthivel-Wainford, Karen (Self-assessment in X-ray Interpretation ;, 2011)
Today many radiographers are trained to report on trauma radiographs. Universities are also training student radiographers to comment on trauma radiographs. It is useful, in some cases essential, that whilst we review the trauma radiograph we also recognise and note any appropriate pathology. For instance a patient attends Accident and Emergency with pain in their knee for several weeks following trauma; the radiographs show no fracture but some signs of a malignant bony tumour, which on further investigation is an osteo sarcoma. As with the other books in the series, this book starts with sev.